2008
DOI: 10.1073/pnas.0801735105
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII accelerates proteolytic cleavage of von Willebrand factor by ADAMTS13

Abstract: Proteolytic processing of von Willebrand factor (VWF) by ADAMTS13 metalloproteinase is crucial for normal hemostasis. In vitro, cleavage of VWF by ADAMTS13 is slow even at high shear stress and is typically studied in the presence of denaturants. We now show that, under shear stress and at physiological pH and ionic strength, coagulation factor VIII (FVIII) accelerates, by a factor of Ϸ10, the rate of specific cleavage at the Tyr 1605 -Met 1606 bond in VWF. Multimer analysis reveals that FVIII preferentially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
131
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 32 publications
8
131
3
4
Order By: Relevance
“…Shim et al (24) and we (22) have demonstrated that lyophilized platelets or coagulation factor VIII (FVIII) alone at physiological concentrations can increase the proteolytic cleavage of VWF by ADAMTS13 by ϳ2-3-fold under mechanically induced fluid shear stresses (22,24). In this study, we show that the combination of the two (FVIII and platelets) at physiological concentrations synergistically accelerates the proteolytic cleavage of VWF by ADAMTS13 under similar conditions.…”
Section: Adamts13 a Member Of The A Disintegrin And Metalloprotease supporting
confidence: 62%
See 3 more Smart Citations
“…Shim et al (24) and we (22) have demonstrated that lyophilized platelets or coagulation factor VIII (FVIII) alone at physiological concentrations can increase the proteolytic cleavage of VWF by ADAMTS13 by ϳ2-3-fold under mechanically induced fluid shear stresses (22,24). In this study, we show that the combination of the two (FVIII and platelets) at physiological concentrations synergistically accelerates the proteolytic cleavage of VWF by ADAMTS13 under similar conditions.…”
Section: Adamts13 a Member Of The A Disintegrin And Metalloprotease supporting
confidence: 62%
“…Patients with aortic stenosis, which generates high flow shear stress in circulation, do exhibit increased VWF proteolysis and reduced VWF multimer size compared with healthy individuals (20,21), suggesting that increased VWF proteolysis is correlated with increased fluid shear stress in vivo. However, under in vitro assay conditions, fluid shear stress alone (22, 23) has only a modest effect on proteolytic cleavage of soluble multimeric VWF by ADAMTS13, suggesting that other proteins or nonprotein cofactors or cellular components may be required for efficient proteolytic processing of soluble multimeric VWF by ADAMTS13.Shim et al (24) and we (22) have demonstrated that lyophilized platelets or coagulation factor VIII (FVIII) alone at physiological concentrations can increase the proteolytic cleavage of VWF by ADAMTS13 by ϳ2-3-fold under mechanically induced fluid shear stresses (22,24). In this study, we show that the combination of the two (FVIII and platelets) at physiological concentrations synergistically accelerates the proteolytic cleavage of VWF by ADAMTS13 under similar conditions.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…This may be especially true on the basis of in vitro studies indicating that FVIII contained in this and other concentrates may physiologically facilitate the cleavage of VWF by ADAMTS13 [19]. Koate V R -DVI has a higher content of functional ADAMTS13 than other tested VWF-FVIII concentrates.…”
Section: Discussionmentioning
confidence: 88%